2018
DOI: 10.1007/s10654-018-0374-z
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors, cardiovascular disease and all-cause mortality in middle-aged and elderly women: a systematic review and meta-analysis

Abstract: Cardiovascular disease (CVD) risk factors, incidence and death increases from around the time of menopause comparing to women in reproductive age. A healthy lifestyle can prevent CVD, but it is unclear which lifestyle factors may help maintain and improve cardiovascular health for women after menopausal transition. We conducted a systematic review and meta-analysis of prospective cohort studies to evaluate the association between modifiable lifestyle factors (specifically smoking, physical activity, alcohol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
158
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(179 citation statements)
references
References 69 publications
12
158
2
7
Order By: Relevance
“…For non-communicable disease outcomes, lifestyle risk factors have been consistently associated with morbidity, mortality and loss of disease-free years of life. [1][2][3][4] There are also population cohort data on possible adverse effects of poor lifestyle on serious respiratory infections. For example, physical inactivity and smoking appear to be independently associated with higher risk of community-acquired pneumonia and pneumonia mortality.…”
Section: Introductionmentioning
confidence: 99%
“…For non-communicable disease outcomes, lifestyle risk factors have been consistently associated with morbidity, mortality and loss of disease-free years of life. [1][2][3][4] There are also population cohort data on possible adverse effects of poor lifestyle on serious respiratory infections. For example, physical inactivity and smoking appear to be independently associated with higher risk of community-acquired pneumonia and pneumonia mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Taken individually, these easily modifiable lifestyle factors are associated with improved survival and reduced risk of major chronic diseases , and several studies have shown that a combination of healthy lifestyle choices has a greater health impact than any single lifestyle factor.…”
Section: Introductionmentioning
confidence: 99%
“…Taken individually, these easily modifiable lifestyle factors are associated with improved survival and reduced risk of major chronic diseases [4,5], and several studies have shown that a combination of healthy lifestyle choices has a greater health impact than any single lifestyle factor. Indeed, simultaneous adherence to low-risk lifestyle factors was reportedly effective in reducing the risk of diseases such as coronary heart disease [6,7], stroke [8], heart failure [9], diabetes [10] and to substantially increase survival in men and women [11,12].…”
mentioning
confidence: 99%
“…This similarity further strengthens the identified risk factors as valuable clinical features healthcare professionals may consider as part of their differential diagnosis. Many of the risk factors identified have previously been reported as major risk factors for morbidity and mortality in chronic diseases worldwide . Therefore, IP may be considered a feature of chronic disease rather than merely a digestive health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Participants Descriptive data Key results Limitations Interpretation Generalisability Funding 12d 12e 13a 13b 13c 14a 14b 14c 15 16a 16b 16c 17 18 19 20 21 22 74,75 Therefore, IP may be considered a feature of chronic disease rather than merely a digestive health issue.…”
Section: Discussion and Other Informationmentioning
confidence: 99%